Guidelines for analyzing and managing the security vulnerabilities of fixed chemical sites. (CCPS guidelines series., 2003)
This new initiative demonstrates a process and tools for managing the security vulnerability of sites that produce and handle chemicals, petroleum products, pharmaceuticals, and related materials such as fertilizers and water treatment chemicals. Includes: enterprise screening; site screening; protection analysis; security vulnerability assessment; action planning and tracking.